2011
DOI: 10.1007/s10096-011-1401-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremic complications of intravascular catheter tip colonization with Gram-negative micro-organisms in patients without preceding bacteremia

Abstract: Although Gram-negative micro-organisms are frequently associated with catheter-related bloodstream infections, the prognostic value and clinical implication of a positive catheter tip culture with Gram-negative micro-organisms without preceding bacteremia remains unclear. We determined the outcomes of patients with intravascular catheters colonized with these micro-organisms, without preceding positive blood cultures, and identified risk factors for the development of subsequent Gram-negative bacteremia. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Some studies have shown that the incidence of bacteraemia was low after removal of IVCs in patients where that tip culture became positive [2,5]. Other authors have postulated that positive tip cultures, in particular those with S. aureus [1,6,7], Candida spp [4], and Gram-negative bacteria [8] with negative concurrent blood cultures, could reflect a recent bloodstream infection, and therefore require a short course of antimicrobial therapy, or point to the potential risk of developing delayed bacteraemia (or fungaemia).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the incidence of bacteraemia was low after removal of IVCs in patients where that tip culture became positive [2,5]. Other authors have postulated that positive tip cultures, in particular those with S. aureus [1,6,7], Candida spp [4], and Gram-negative bacteria [8] with negative concurrent blood cultures, could reflect a recent bloodstream infection, and therefore require a short course of antimicrobial therapy, or point to the potential risk of developing delayed bacteraemia (or fungaemia).…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular catheters are a major source of bloodstream infections in hospitalized patients. The prevalence of catheter-related infections is approximately five episodes per 1,000 catheter days in Europe 16 and one to six episodes per 1,000 catheter days in the United States. 1 These infections often result in increased morbidity and mortality and increase costs considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Three retrospective [136,182,186] and two prospective observational studies [187,188] on bacterial colonisation recommended a duration of at least 3 days of antibiotic therapy, with at least one of the antibiotics adapted to antibiotic susceptibility testing. Three out of five studies, including two prospective studies, each targeting a particular microorganism, P. aeruginosa and A. baumannii, showed a marked reduction of bacteraemia rates.…”
Section: Expert Opinionmentioning
confidence: 99%